Integrasi Pendidikan Karakter dalam Pelaksanaan Pembelajaran Pendidikan Agama Islam - Hajriana; Helenawati (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2017)
The decline of morality is the concern of the education by reforming the educational system in the form of the application of character education that is integrated into the school implementation system of education, including the implementation of learning. Islamic Education Teachers in Vocational High School (SMK) Muhammadiyah Loa Janan also attempted to integrated character education into the implementation of learning. This study described the process or ways integrating character education into the implementation of learning Islamic Education. The results of this study illustrated that the integration of character education in the implementation of Islamic Education in Vocational High School (SMK) Muhammadiyah Loa Janan implemented by integrate character education into the process of implementation of learning through exemplary process and self-awareness of students by giving advice and motivation to familiarize self-executing the values ​​of characters that want to be implanted into the students in everyday.